Encapsulating peritoneal sclerosis: pathophysiology and current treatment options - Jagirdar, Rajesh M.; Bozikas, Andreas; Zarogiannis, Sotirios G.; Bartosova, Maria; Schmitt, Claus P.; Liakopoulos, Vassilios (International journal of molecular sciences, 2019)
Encapsulating peritoneal sclerosis (EPS) is a life-threatening complication of long-term peritoneal dialysis (PD), which may even occur after patients have switched to hemodialysis (HD) or undergone kidney transplantation. The incidence of EPS varies across the globe and increases with PD vintage. Causative factors are the chronic exposure to bioincompatible PD solutions, which cause long-term modifications of the peritoneum, a high peritoneal transporter status involving high glucose concentrations, peritonitis episodes, and smoldering peritoneal inflammation. Additional potential causes are predisposing genetic factors and some medications. Clinical symptoms comprise signs of intestinal obstruction and a high peritoneal transporter status with incipient ultrafiltration failure. In radiological, macro-, and microscopic studies, a massively fibrotic and calcified peritoneum enclosed the intestine and parietal wall in such cases. Empirical treatments commonly used are corticosteroids and tamoxifen, which has fibrinolytic properties. Immunosuppressants like azathioprine, mycophenolate mofetil, or mTOR inhibitors may also help with reducing inflammation, fibrin deposition, and collagen synthesis and maturation. In animal studies, N-acetylcysteine, colchicine, rosiglitazone, thalidomide, and renin-angiotensin system (RAS) inhibitors yielded promising results. Surgical treatment has mainly been performed in severe cases of intestinal obstruction, with varying results. Mortality rates are still 25–55% in adults and about 14% in children. To reduce the incidence of EPS and improve the outcome of this devastating complication of chronic PD, vigorous consideration of the risk factors, early diagnosis, and timely discontinuation of PD and therapeutic interventions are mandatory, even though these are merely based on empirical evidence.